VD_FINDINFO Décision / 2012 / 15 vom 5. Januar 2012 - VD Tribunal cantonal (2012)
DIFFAMATION, PREUVE DE LA VÉRITÉ, RESPONSABILITÉ PÉNALE DE LA PRESSE | 173 ch. 1 CP, 173 ch. 2 CP, 173 ch. 3 CP, 28 CP, 319 CPP (CH)